IMPROVING STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXTS BY USING SMALL GROUP DISCUSSIONS AT THE GRADE X A MA KMI OF DINIYYAH PUTERI PADANG PANJANG - Dartini, Dartini (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2009)
Most of the students got difficulties in comprehending narrative reading texts. It could be seen from the result of exams given by teacher. Thus, this study is aimed at finding out (1) To what extent Small Group Discussion could improve the students’ reading comprehension on narrative text at tenth grade MA KMI of Diniyyah Puteri Padang Panjang and (2) What factors could influence the students’ reading comprehension of narrative text by applying small group discussions. The Classroom Action Research (CAR) has been conducted in three cycles. The participants were twenty three students of class X A MA KMI of Diniyyah Puteri. The data were collected by giving reading comprehension tests, observation, interview and field notes. They were analyzed quantitatively and qualitatively. The findings have shown that (1) Small Group Discussions could improve students’ reading comprehension of narrative text at class X A MA KMI Diniyyah Puteri Padang Panjang, and (2) factors which influence students’ reading comprehension were limited number of students, reading materials and giving rewards to increase students’ participations and motivations, monitoring and group discussion activities.